Karakteristik Menara Pendingin dengan Bahan Isian Ijuk - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Abstract In this study the characteristic of a water cooling tower by using the palm fibre as the packing material have been investigated experimentally. The experiments were carried out in a rectangle glass tower oj 81 cm2 cross sectional area and 100 cm' height. The packing used was constructed of 8 palm-jibre ropes (of about 0,6 cm diameter), zigzag vertically, and then it placed above the stainless steel support on the tower bottom. Its type has 28,3.10-4 kg weighs of rope every m3 volume of the packing. The experimental results show that the increasing of the water inlet temperature and the packing height cause the increasing of the tower characteristic. Mean while, the increasing of the water/air mass flow rate ratio causes the decreasing of the tower characteristic. The tower characteristic is as afimction of the investigated variables which expressed as: NTU = 3,35.10-3 (m,/mq}-0.995(Z/,5050 (TwJ'.J643 with the relative error of5,5%. This equation is valid for the range of variables, as m'/ma which is ranged from 4,46 to 9,48, Z which is ranged from 30 to 90 cm, Twiwhich is ranged from 50 to 60°C. The, mean effecti~eness of the heat transfer were calculated to be 25,9%. Keywords: Cooling tower, characteristic, effectiveness, palm-jibre ropes.